BLOOD PRESSURE VARIABILITY AND CLINICAL CHARACTERISTICS OF PATIENTS HOSPITALIZED FOR ACUTE MYOCARDIAL INFARCTION. (June 2018) - Konstantinou, K.; Tsioufis, K.; Mantzouranis, M.; Koumeli, A.; Fragoulis, C.; Vogiatzakis, N.; Dimitriadis, K.; Kasiakogias, A.; Tousoulis, D.
Abstract : Objective: The aim of the present study was to assess blood pressure variability (BPV) in patients hospitalized for acute myocardial infarction. Design and method: We studied 75 patients (76% males, age 65 ± 13 years) who were hospitalized because of ST-elevation myocardial infarction (STEMI) and Non ST–elevation myocardial infarction (NSTEMI). All patients underwent baseline estimation of clinical and laboratory parameters during their hospitalization. Additionally, BPV was estimated based on double daily measurements of BP during hospitalization and with 24-hour ambulatory BP monitoring during the third day of hospital stay. The parameters of BPV analyzed were: a) standard deviation (SD) of systolic BP (24-h, daytime and nighttime), b) SD of diastolic BP (24-h, daytime and nighttime) and c) the coefficient of variation (CV) of systolic BP (24-h, daytime) and d) the average real variability (ARV) of systolic and diastolic BP across 24-h. Results: From the total population, 20% had family history of cardiovascular events, 72% were hypertensives, 32% had diabetes, 51% were smokers and 32% had previous history of coronary artery disease. Regarding the type of myocardial infarction, 37% were admitted for STEMI and 55% had coronary revascularization. Focusing on the mean systolic and diastolic BP and their SD the values were 72 ± 6.1mmHg, 127 ± 11.4mmHg and 74.5 ± 6.5mmHg, respectively. From the ambulatory BP the daytime, nighttime and total SD of systolic BP was 11.3 ± 2.8mmHg, 9.8 ± 3.1mmHg and 11.7 ± 2.9mmHg, respectively. Moreover, ARV was 9.31 ± 2.1mmHg while CV was 10.21 ± 26 %. The type of MI (STEMI and NSTEMI) was significantly related to systolic and diastolic ARV (r = 0.29, p = 0.012 and r = 0.28, p = 0.014, respectively). Conclusions: In patients admitted for acute myocardial infarction there is a relationship between the ARV and the type of myocardial infarction. These findings suggest differential impact of hemodynamic load on the cardiovascular system in patients with STEMI and NSTEMI.